Persistence of myopathy in Cushing's syndrome: evaluation of the German Cushing's Registry. Issue 6 (June 2017) - Berr, Christina M; Stieg, Mareike R; Deutschbein, Timo; Quinkler, Marcus; Schmidmaier, Ralf; Osswald, Andrea; Reisch, Nicole; Ritzel, Katrin; Dimopoulou, Christina; Fazel, Julia; Hahner, Stefanie; Stalla, Günter K; et al.
Abstract : Background: Cushing's syndrome (CS) is characterized by an excessive secretion of glucocorticoids that results in a characteristic clinical phenotype. One feature of clinical hypercortisolism is breakdown of protein metabolism translating into clinical consequences including glucocorticoid-induced myopathy. While surgery is effective in control of cortisol excess, the effect of biochemical remission on muscular function is yet unclear. Methods: In a cross-sectional study we analyzed 47 patients with CS during the florid phase (ActiveCS). 149 additional patients were studied 2–53 years (mean: 13 years) after surgery in biochemical long-term remission (RemissionCS). Also, 93 rule-out CS patients were used as controls (CON). All subjects were assessed for grip strength using a hand grip dynamometer and underwent the chair rising test (CRT). Results: Hand grip strength (85% vs 97% of norm, P  = 0.002) and the CRT performance (9.5 s vs 7.1 s, P  = 0.001) were significantly lower in ActiveCS compared to the CON group. Six months after treatment grip strength further decreased in CS ( P  = 0.002) and CRT performance remained impaired. The RemissionCS group (mean follow-up 13 years) had reduced hand grip strength (92% compared to normal reference values for dominant hand, P  < 0.001). The chair rising test performance was at 9.0 s and not significantly different from the ActiveCS group ( P  = 0.45). Conclusion: CS affects muscle strength in the acute phase, but functional impairment remains detectable also during long-term follow-up despite biochemical remission.